Acute Macular Neuroretinopathy following Oral Intake of Adrenergic Flu Treatments - Dinu Stanescu-Segall; Chong Yap; Ben J.L. Burton (Case Reports in Ophthalmology, 2018)
Purpose: The purpose of this study was to report a case series of patients with acute macular neureretinopathy in which patients concomitantly used ephedrine or pseudo-ephedrine. Methods: This is a retrospective case review. Results: Two patients with retinal findings consistent with acute macular neuroretinopathy are presented. Conclusion: Acute macular neuroretinopathy should be considered in any young patient with unexplained loss of vision and exposed to direct or indirect adrenergic stimulation.